Analysis Revenues Of Casing Cover Business Inslipper Material In Medan - Hanifa Khairiah; Hanifa Ayu Armayani; Mahbud Farid Lubis; Muhammad Ridwan; Akbar ihza vito siregar (JASc (Journal of Agribusiness Sciences), 2019)
Mobile phones or cellphones are one of the most developed communication technologies in the world. Many countries in the world are competing to produce cellphones. This happens because the demand from the market is so large. Mobile phone gloves or cellphone cases as one of the accessories used by consumers for a number of reasons, including protecting cellphones from abrasions, reducing the risk of falls, for style, etc. The aim of the study was to make people's mobile phones safer from the fall because the public now lacked protecting their own cellphones, and another goal was to determine the criteria for mobile gloves to suit the needs and desires of consumers. The type of research method chosen was descriptive analysis. the method that functions to describe or give an overview of the object under study through data or samples that have been collected as it is without doing analysis and making conclusions that apply to the public ... Income at phpcase.id is interpreted as the difference between the amount of revenue and costs incurred (total cost. Table 5 is a list of income from phpcase.id research results. Table 5. Average Business Income phpcase.id in medan city in 2019 that phpcase.id in Medan city earns income from the case business of Rp.5,200,000. Conclusion what can be taken is the product the average per pcs of the phpcase.id business in Medan city is 500 pcs with a selling price of Rp. 14,000 / pcs, the total business income of phpcase.id is Rp. 7,000,000, a variable that has a significant effect on phpcase.id's business income in the city Medan, namely raw materials, production costs and production results.